The Landfill of Early Roman Jerusalem The 2013‒2014 Excavations in Area D3 - Gadot, Yuval 1967- (Ancient Jerusalem Publications, 2022)
This is the story of the landfill that operated in Jerusalem during the first century CE and served as its garbage dump during the ca. 50-year period that followed Jesus's crucifixion through to the period that led to the great revolt of the Jews just prior to the city's destruction.The book presents an extensive investigation of hundreds of thousands of items that were systematically excavated from the thick layers of landfill. It brings together experts who conducted in-depth studies of every sort of material discarded as refuse-ceramic, metal, glass, bone, wood, and more. This research presents an amazing and tantalizing picture of daily life in ancient Jerusalem, and how life was shaped and regulated by strict behavioral rules (halacha). The book also explores why garbage was collected in Jerusalem in so strict a manner and why the landfill operated for only about 50 years. Half a century of garbage from Early Roman-period Jerusalem provides an abundance of new data and new insights into the ideological choices and new religious concepts emerging and developing among those living in Jerusalem at this critical moment. It is an eye-opener for archaeologists, historians, anthropologists, and theologians, as well as for the general reader